Nutrient fluxes and environmental performance indicators for a pasture-based dairy system (Acta Scientiarum. Animal Sciences, 2020)
The aim of this study was to evaluate the nutrient fluxes for lactating cows in a pasture-based dairy system and the impact of a nutritional management strategy on the environmental performance indicators. Fourteen lactating cows were divided into two experimental groups with seven animals each. The nutritional managements were a diet containing 20% crude protein (Group 1) and a diet with adjusted protein (Group 2). The nutrient budget was calculated on a monthly basis for nitrogen, phosphorus, and potassium. The nutritional strategy of adjusted protein reduces the total surplus in the lactation period for nitrogen by 7.6% and for phosphorus by 6.3%. The total potassium surplus of the adjusted protein group was 8.5% higher. The average nitrogen use efficiency was 21% for group 1 and 22.7% for group 2. Phosphorus use efficiency ranged from 13.4 to 35% for group 1 and from 15.5 to 34% for group 2 and potassium average use efficiency was 14.2% for group 1 and 12.6% for group 2. Nutritional management reduced nitrogen and phosphorus surpluses as well as the values of the environmental performance indicator. Based on this, it is possible to improve the environmental efficiency of dairy systems through improved nutritional management.